Three-Dimensional Scanning Virtual Aperture Imaging with Metasurface - Zhan Ou; Yuan Liang; Hua Cai; Guangjian Wang (Sensors)
Metasurface-based imaging is attractive due to its low hardware costs and system complexity. However, most of the current metasurface-based imaging systems require stochastic wavefront modulation, complex computational post-processing, and are restricted to 2D imaging. To overcome these limitations, we propose a scanning virtual aperture imaging system. The system first uses a focused beam to achieve near-field focal plane scanning, meanwhile forming a virtual aperture. Secondly, an adapted range migration algorithm (RMA) with a pre-processing step is applied to the virtual aperture to achieve a 3D high-resolution reconstruction. The pre-processing step fully exploits the feature of near-field beamforming that only a time delay is added on the received signal, which introduces ignorable additional calculation time. We build a compact prototype system working at a frequency from 38 to 40 GHz. Both the simulations and the experiments demonstrate that the proposed system can achieve high-quality imaging without complex implementations. Our method can be widely used for single-transceiver coherent systems to significantly improve the imaging depth of field (DOF).